A Characteristic Boundary Condition for Multispeed Lattice Boltzmann Methods (Communications in Computational Physics, 2023)
We present the development of a non-reflecting boundary condition, basedon the Local One-Dimensional Inviscid (LODI) approach, for Lattice Boltzmann Models working with multi-speed stencils.We test and evaluate the LODI implementation with numerical benchmarks, showing significant accuracy gains with respect to the results produced by a simple zero-gradient condition. We also implement a simplified approach, which allows handlingthe unknown distribution functions spanning several layers of nodes in a unified way,still preserving a comparable level of accuracy with respect to the standard formulation.